Inclusive Responses to the HIV and AIDS Challenge : Experiences from the Indian IT Sector - World Bank Institute; Confederation of Indian Industry; Indian Business Trust for HIV/AIDS (World Bank, Washington, DC, 2017)
India is experiencing a period of high economic growth and rapid social and demographic change. There is increasing concern about the manner in which this transformation is impacted by the HIV/AIDS epidemic. While the Government of India has taken significant measures to curb the spread of HIV/AIDS, much remains to be done. Given the complexity of the challenge, an effective response requires the engagement of all sectors. The private sector, alongside other stakeholders, can play an important part not only by contributing to the efforts for HIV/AIDS prevention and the reduction of stigma and discrimination, but also for the care, support and treatment of Persons Living with HIV/AIDS (PLHA). The report presents challenges, good practices and success stories about how Informational Technology (IT) companies in India are addressing the issues of HIV/AIDS. It demonstrates the mounting will and commitment of IT leaders to respond to the epidemic. The IT industry in India is young in terms of both its stage of development and the age of its workforce which averages 18-35 years. Reflecting the composition of the sector, the report documents the experiences not only of large companies in India's IT sector, but also of small and medium enterprises (SMEs). Each company has used different approaches to address HIV/AIDS among its workforce including community outreach activities. By capturing these companies' experiences, the report seeks to foster a more active response to HIV/AIDS from India's IT community and to encourage new partnerships to leverage the goodwill and competencies of this sector.